Dual-crosslinked hyaluronic acid hydrogel with self-healing capacity and enhanced mechanical properties. (1st February 2023) - Zhang, Mengfan; Chen, Xiao; Yang, Kaidan; Dong, Qi; Yang, Hongjun; Gu, Shaojin; Xu, Weilin; Zhou, Yingshan
Abstract: Self-healing hydrogels can repair their cracks, and restore their original properties. However, self-healing hydrogels usually face low mechanical strength and poor stability. By the dual crosslinking strategy, a self-healing hyaluronic acid-based hydrogel with enhanced strength was fabricated by dynamic acylhydrazone linkages between aldehyde-modified maleic sodium hyaluronate and 3, 3′-dithiobis (propionylhydrazide) and subsequent photopolymerization among maleic groups in the hydrogel network. The hydrogels exhibit fast gelation and excellent self-healing capability due to the dynamic and reversible characteristics of acylhydrazone and disulfide linkages. Furthermore, the dual crosslinking increase the mechanical strength of the hydrogels and prolong their stabilization time. Swelling behaviors, morphology, and mechanical properties could be adjusted by altering the molar ratio of –NH–NH2 /–CHO. Besides, the hydrogels displayed interesting pH-responsiveness and cytocompatibility. The hydrogels have potential applications in cell culture, drug delivery, and 3D bioprinting. Graphical abstract: Unlabelled Image Highlights: Hyaluronate hydrogel was obtained by acylhydrazone linkages and photocrosslinking. Excellent self-healing ability was acquired via dual reversible crosslinking. Enhanced strength promoted hydrogel stabilization. These hydrogels were pH-responsive and cytocompatible.